EVALUATION OF ANTICONVULSANT ACTIVITY OF ETHANOL LEAF EXTRACT OF FICUS SYCOMORUS LINN IN PENTYLENETETRAZOLE AND STRYCHNINE INDUCED SEIZURES IN MICE - MOH’D A.S.; ELON I.R; MIDALA T.A.S; MILAGAWANDA H.H; TIMOTHY S.Y (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
Epilepsy is a chronic and often progressive disorder characterized by the occurrence of epileptic seizures, affecting about 50 million people worldwide. The prescribed synthetic drugs for the treatment of epilepsy are associated with severe side effects and addiction liabilities upon long term uses. Thus, researchers around the globe are searching for newer, effective and safer drugs from natural resources. Ficus sycomorus Linn. (Moraceae) is used traditionally in Northern Nigeria for the management of epilepsy without any scientific validation. The aim of this study is to evaluate the phytochemical constituents and the anticonvulsant activity of the ethanol leaf extract of F. sycomorus L. in mice. The basic phytochemical screening was carried out based on some standard procedures, while Lorke’s method was used to determine the lethal dose that kills 50% of laboratory animals. Pentylenetetrazole and strychnine were used to induce seizures in mice for the anticonvulsant screening.The plant extract revealed the presence of tannins, saponins, carbohydrates, alkaloids, flavonoids, steroids, terpenoids and cardiac glycosides. The intraperitoneal LD50 in mice was estimated to be >2900 mg/kg body weight. The plant extract at the highest tested dose protected the animals from death against the chemically induced seizures by pentylenetetrazole and strychnine while the time for onset of convulsion was dose dependent. An extremely significant difference (p<0.05) in the mean onset of convulsion was observed at highest dose of the extract against PTZ and strychnine when compared to the control and the mice were protected from death by the extract. However, the extract showed better activity against strychnine induced seizures. The data suggest that the ethanol leaf extract of F. sycomorus, at the tested doses and under the experimental conditions reported, contains many phytochemical constituents that may be responsible for the anticonvulsant activity. Thus, justifying the ethnomedical use of this plant extract in the management of epilepsy as claimed by the traditional medicine practitioners.